UPFC Integrated With Battery Energy Storage Systems for Stability Improvement - Saravanan, K; Berhanu, Dawit Leykuen; Somano, Getnet Zewde (Asian Journal of Energy Transformation and Conservation, 2014)
In Electrical Power network, consumer loads are time to time variation in existing transmission system. Loads will not constant means, power quality issues there such as voltage have been flickering and deviations in power supply which make some of the electronic equipments and domestic devices highly sensitive to it . Unified Power Flow Controller (UPFC) is most promising new technologies among the many FACTS devices which can improve the power system operation and power quality problems. To avoid such problems need to find out devices that can provide a backup during the time of voltage sags and such deviations. UPFC joined with batteries through dc-dc chopper have been introduced to improve their ability to exchange real power. The active power injected into the DC-bus is controlled by varying the duty cycle of the switches in the dc-dc chopper while the battery is discharging.